2023
DOI: 10.1002/ppul.26606
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a respiratory therapist driven high flow nasal cannula management protocol for pediatric critical asthma patients

Danielle K. Maue,
Daniel T. Cater,
Colin M. Rogerson
et al.

Abstract: IntroductionThis study aimed to determine if a respiratory therapist (RT)‐driven high flow nasal cannula (HFNC) protocol could decrease duration of HFNC use, pediatric intensive care unit (PICU) and hospital length of stay (LOS), and duration of continuous albuterol use in pediatric patients with critical asthma.MethodsThis was a quality improvement project performed at a quaternary academic PICU. Patients admitted to the PICU between 2 and 18 years of age with a diagnosis of asthma requiring continuous albute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The lack of a meaningful improvement observed by Maue et al 18 on duration of HFNC therapy, PICU and hospital LOS, and duration of continuous albuterol treatment after PDSA cycle 2 was likely multifactorial. First, the team may have already fully realized the potential benefit from their protocol and HFNC weaning was not a significant driver of LOS.…”
mentioning
confidence: 88%
See 4 more Smart Citations
“…The lack of a meaningful improvement observed by Maue et al 18 on duration of HFNC therapy, PICU and hospital LOS, and duration of continuous albuterol treatment after PDSA cycle 2 was likely multifactorial. First, the team may have already fully realized the potential benefit from their protocol and HFNC weaning was not a significant driver of LOS.…”
mentioning
confidence: 88%
“…Additional challenges in comparing various studies on HFNC in pediatric critical asthma arise from variations in the entry criteria used to define the study cohorts. For instance, Gates et al 12 evaluated HFNC in a critical asthma cohort with an Modified Pulmonary Index Score (MPIS) ≥8 and demonstrated a longer duration of continuous albuterol by 6 h and longer PICU LOS by 14 h compared to the study conducted by Maue et al 18 However, interestingly, the overall hospital LOS was shorter in the Gates study 12 . Furthermore, other studies have also reported shorter durations of continuous albuterol, PICU LOS, and hospital LOS in comparison to the current report 20,21 .…”
mentioning
confidence: 99%
See 3 more Smart Citations